TYPES OF DAIRY PRODUCTS AND THEIR CLASSIFICATION - Kushnazarova Shoxidaxon Kosimovna; Valijonova Aziza (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides information on the types of dairy products